m-7+48-5=

Simple and best practice solution for m-7+48-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-7+48-5= equation:


Simplifying
m + -7 + 48 + -5 = 0

Reorder the terms:
-7 + 48 + -5 + m = 0

Combine like terms: -7 + 48 = 41
41 + -5 + m = 0

Combine like terms: 41 + -5 = 36
36 + m = 0

Solving
36 + m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + m = 0 + -36

Combine like terms: 36 + -36 = 0
0 + m = 0 + -36
m = 0 + -36

Combine like terms: 0 + -36 = -36
m = -36

Simplifying
m = -36

See similar equations:

| 3k+8=35 | | -3d+3=-27 | | 4-4t=-32 | | -8+3k=-5 | | 4n+3=47 | | 4n-4=44 | | 5b+7=27 | | 4t+5=-19 | | 4k-9=-5 | | -7n+6=-36 | | 2b+7=-3 | | -3k+6=-6 | | 6w+5=23 | | 8y(-2y^6)= | | 7-4n=-25 | | 3*(x+1)+2=-4 | | -2x+1=-23 | | -2d+9=29 | | 7a-9=-9 | | -10+6b=-58 | | 4d-10=-14 | | 9+7n=-26 | | 4+7k=-80 | | 80/0.5 | | 7-2x=3x-2x+4 | | 4+6t=64 | | 5t-9=-4 | | 7d+10=66 | | 9-5m=4 | | 3k-9=24 | | 7b-3=25 | | 3k-9=-15 |

Equations solver categories